Dampak Penggunaan Media Sosial terhadap Kecemasan Mahasiswa di Universitas Negeri Manado : Penelitian - Marssel M. Sengkey; Nova Lisye Sinaulan; Stefani Tendean; Herlina Sianly Ninda; Joel Mangantes; Yerikho Shefa Pratasik (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology has made social media an integral part of students' lives. While offering various benefits in terms of communication and access to information, excessive use of social media has the potential to cause negative effects on mental health, particularly anxiety. This study aims to examine the relationship between social media use and anxiety levels among students using a literature review approach. The literature analyzed was obtained from various relevant scientific journals published within the past five to ten years. The findings indicate that students in the emerging adulthood phase are vulnerable to anxiety due to digital social pressures, such as Fear of Missing Out (FOMO), the need for social validation, and the tendency to use social media as an escape from academic stress. Previous studies, both quantitative and qualitative, have confirmed a significant correlation between the intensity of social media use and anxiety symptoms. Therefore, it is important for students to manage their social media use wisely and for educational institutions to provide promotional and preventive support to maintain students' mental health in this digital age.